2007
DOI: 10.1016/j.jconrel.2006.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and pharmacokinetics of colon-specific HPMA copolymer–9-aminocamptothecin conjugate in mice

Abstract: A water soluble N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer -9-aminocamptothecin (9-AC) conjugate was designed for oral colon-specific drug delivery for the treatment of colon cancer. Comparative studies between the polymer conjugate and free drug have been performed to assess their biodistribution and pharmacokinetics in mice. After oral administration of equal doses of the polymer conjugate or free 9-AC, the drug concentrations in major organs at fixed time points were determined using an HPLC-fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…Previously, we reported the metabolism of 9-AC in liver of mice and identified one liver metabolite produced by hydroxylation of the amino group of 9-AC (14). To quantitatively determine the drug hepatic availability (F h ) in rats (n = 4), liver perfusion was performed.…”
Section: Liver Metabolism and Availabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we reported the metabolism of 9-AC in liver of mice and identified one liver metabolite produced by hydroxylation of the amino group of 9-AC (14). To quantitatively determine the drug hepatic availability (F h ) in rats (n = 4), liver perfusion was performed.…”
Section: Liver Metabolism and Availabilitymentioning
confidence: 99%
“…The absorbed fraction of 9-AC was calculated as 0.63±0.14 based on the difference between the starting and remaining concentration in the cecum. It was reported that 9-AC was metabolized via the cecal wall after absorption from the cecum (14). The cecal availability (F c ) of 9-AC was calculated as 0.35±0.12 according to Eq.…”
Section: Cecum Metabolism and Availabilitymentioning
confidence: 99%
See 3 more Smart Citations